KETERKAITAN PARITAS DAN UMUR IBU DENGAN DIASTASIS MUSCULUS RECTI ABDOMINIS (DMRA) - mariah ulfah (Universitas Harapan Bangsa Purwokerto, 2016)
Background: Physiological Adaptation to pregnancy was dramatic and often underestimated. The time and intensity of change varies among different systems.Early in pregnancy, uterine growth occurs due to hyperplasia and hypertrophy ofmyometrium cells under the influence of estrogen. During the first few months ofpregnancy, uterine wall becomes much thicker and softer, at the age of justmonths uterus into a muscular pouch with soft walls, easy curved and thickness of0.5-1 cm or less (Margaret A; 2009), in addition to the hormonal changes causedby relaxin, progesterone and estrogen combines with the growth of the uterus maycause abdominal stretch the muscles bibs, affecting most of the rectus abdominismuscles that cause separation (diastasis recti abdominis). These postural changescan affect the placement angle of pelvic and abdominal muscles, affectingpostural biochemistry. If this continues, diastasis rectiadbominis vectorakanmenyebabkan a loss in muscle strength, and will cause a reduction in musclestrength at the time of contraction that would cause labor becomes longer(Meredy, 2000). Therefore, the authors interested in examining the